ESTIMATION OF GENE ACTION FOR FRUIT YIELD AND MORPHOLOGICAL TRAITS IN GREENHOUSE CUCUMBER BY MATING DESIGNS - Maryam Golabadi; Pooran Golkar; Sezai Ercisli (Acta Scientiarum Polonorum: Hortorum Cultus, 2017)
In this study, gene action, genetic variances (δ2A and δ2D ), and combining abilities were estimated for fruit related traits using North Carolina Design ІІ (NCD ІІ) for ten different parental genotypes of greenhouse cucumber. This experiment was performed over a two-year period from 2014 to 2015. The variance components of male, female, and male × female were found to be significant for all the studied traits in a combined analysis of variance. Genetic component analysis showed that fruit diameter, fruit length, total fruit weight, fruit number in early picking and fruit number per node were predominantly under the additive gene action, but internode length and plant height were under the dominance of gene action. Male × female × environment interaction was significant for total fruit weight. The highest general combining ability (GCA) effect for total fruit yield was observed in Zohal (male parent) and YaldaR2 (female parent) genotypes. GCA estimation revealed that male parent of Adrian 4510 provided good general combiners for total fruit number. Specific combining ability (SCA) estimation determined the suitability of Janeete × Adrian 4510. Salar hybrid exhibited higher positive SCA effects for total fruit yield and total fruit number in early picking.